REFORMASI BIROKRASI DESA PANGGUNGHARJO - DANANG SEPTIYANTO (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
Bureaucracy has an important role in running the government at all levels of government. However, the quality of the bureaucracy, especially in village government, is generally still poor. Based on these conditions, this study examines the efforts made by the Panggungharjo Village Government, Sewon District, Bantul Regency under the leadership of Wahyudi Anggoro Hadi as the village head in carrying out Bureaucratic Reform. Data collection techniques using observation, interviews, literature study and documentation. The data analysis method of this research is descriptive qualitative analysis. The results show that the Bureaucratic Reform in Panggungharjo Village aims to restore the trust of the people of Panggunghajo Village to the Panggungharjo Village Government considering the bureaucracy that seems slow, corrupt and biased by elite interests. To realize the Bureaucratic Reform, various efforts were carried out, namely exemplary, expanding public services in order to change the relationship between the village government and the community, Public Administration Services through One-Stop Services, building a new culture of bureaucracy by providing rewards and punishments, the openness of public information and increasing quality of Human Resources (HR) of village officials. Bureaucratic reform has implications for improving the performance of the Panggungharjo Village Government so that the Panggungharjo Village Government has received many awards both from within and outside the country.